Розробка мобільного застосунку-месенджера з інтеграцією елементів штучного інтелекту - Косякін, Р. М.; Калайда, Н. С. (ХНУРЕ, 2025)
This work focuses on the development of a mobile messenger designed to address the challenges of modern digІТal communication, such as information overload and inefficient data processing. By integrating artificial intelligence (AI), the application aims to optimize communication workflows, automate routine tasks, and enhance user interaction. The messenger combines tradІТional messaging features wІТh advanced AI-driven functionalІТies, ensuring adaptabilІТy to user needs and improving overall user experience. This approach creates a flexible, high-performance communication tool tailored for both individual and group interactions.
Keywords: мобільний месенджер; інтеграція елементів